Application of Relaxation Therapy on Chronic Pain in the Elderly with Hypertension at UPT PSTW Jember: A Case Study - Andrena, Daniela; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2023)
The elderly are over 60 and experience physical, mental, and social changes. A decrease in physical strength, endurance, and appearance indicates physical changes in the elderly. The elderly are at risk of experiencing hypertension due to several factors, decreased elasticity and accumulation of collagen in the aortic wall, neurotransmitter imbalance due to depression, and an unhealthy lifestyle during youth. This study aims to determine the impact of applying relaxation therapy to chronic pain problems in the elderly. The design of this case study is descriptive qualitative with a nursing care process approach. This study took a sample of Mr. M, who has chronic pain problems with hypertension at UPT PSTW Jember. This research was carried out for seven days with the application of therapy for six days on December 4-10 2022. Data collection was carried out using interviews and observation. The evaluation of this intervention therapy action uses the NRS pain scale, blood pressure measurement, and pulse count. Relaxation therapy using the spiritual-emotional freedom technique (SEFT) has made a difference in chronic pain problems in the elderly with hypertension. This is evidenced by decreased pain scale and blood pressure after therapy.